Methane Gas Adsorption Capacity Of Carbon Materials For Adsorbed Natural Gas Applications - R. Alkhatib, Ma’an Fahmi (2007)
Adsorbed natural gas (ANG) technique was used in this study to test the adsorption capacity of carbon materials fro methane gas storage. An adsorption system based on volumetric method was designed and fabricated for this purpose. The carbon materials used were Malaysian industrial activated carbon produced from palm kernel shell and coconut shells. These materials have not been thoroughly investigated for ANG applications. Also a new material which is a composite of CNTs and activated carbon (ACNT) produced in this work along with commercial CNTs were investigated as ANG storage media. ACNT was produced using chemical vapour deposition (CVD) method using activated carbon as catalyst substrate. The presence of activated carbon, besides being substrate, served as auxiliary storage media. This method successfully produced CNTs with diameters ranged form 25 to 70 nm and lengths, mostly, of more than 10 μm. These long tubes could be a result of the long reaction time (3 hours), thus if shorter CNTs are required, shorter reaction times should be applied. The adsorption storage experiments were run at pressures up to 50 bar and temperatures of 30, 40 and 50 °C. The adsorption capacity on mass basis (at 35 bar and 30 °C) ranged from as low as 1.48 mmol/g for com-CNT to 6.20 mmol/g for CSAC3. ACNT showed a relatively high adsorption capacity of 4.51 mmol/g. The results indicate that there is a general trend of increasing in adsorption capacity with increasing micropore volume. However, micropore size distribution (MPSD) must be taken into account in evaluating the adsorbents. The adsorption capacity on volume basis (V/V) ranged from 51.57 for com-CNT to 106.46 for CSAC2. These values are still below the targeted 150 V/V. While some adsorbents showed the highest adsorption capacity on mass basis compared to others (CSAC3 versus CSAC2), yet their capacity on volume basis was lower as a result of their lower bulk density. This showed the importance of this parameter in ANG applications. The methane delivered values were 7-25% lower than the volumetric methane storage capacity. The high retention of methane gas at atmospheric pressure by some adsorbents could be explained by their narrow MPSD. Accordingly, the narrow MPSD helps in increasing the adsorption capacity, yet, the very narrow MPSD will increase the amount of gas retained.Several single component isotherm models were used to fit the experimental adsorption isotherm data. All the adsorption isotherm models used showed a good fit to the experimental data. However, Langmuir isotherm model was chosen to be used in the dynamic model to restrict the already heavy computational load from being unrealistic. The experimental data obtained from the storage and delivery tests were compared to those obtained from process simulation using a dynamic model. The simulation model was run using the measured equilibrium data as input parameters. A good agreement was observed between experimental and simulated results. Pressure and temperature histories were acceptably well predicted